2001
DOI: 10.1590/s0004-282x2001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Familial cancer: depressed NK-cell cytotoxicity in healthy and cancer affected members

Abstract: Depressed natural killer (NK) cell activity has been showed in family members of patients with different types of cancer. The present work aimed to evaluate T cell subsets and NK cell cytotoxic activity in 15 members of a family with high incidence of tumors, such as glioblastoma, gastric, pancreas and colon rectal carcinoma, chronic myelocitic leukemia, melanoma and osteoblastoma. As controls, 19 healthy subjects with the age range equivalent were studied. The enumeration of CD3+ lymphocytes and their CD4+ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…This hypothesis is indirectly supported by a study showing that individuals with lower NK cytotoxic activity in peripheral blood had a higher incidence of cancer (n=3,500 with 11-year follow-up) 39 ). Similarly, previous studies showed that impaired NK cell activity was found in family members of patients with different types of cancer ( 40, 41, 42 ). Importantly, such inherited defects in NK cells, APP and Wnt pathways were repeatedly observed between non-cancer and cancer individuals (Fig 2b, Supplementary Fig 9), between TIME-rich and TIME-intermediate/-poor patients (Fig 2a, Supplementary Fig 4, Fig 1d), suggesting that these individuals were highly selected for tumorigenesis and metastasis.…”
Section: Resultssupporting
confidence: 67%
“…This hypothesis is indirectly supported by a study showing that individuals with lower NK cytotoxic activity in peripheral blood had a higher incidence of cancer (n=3,500 with 11-year follow-up) 39 ). Similarly, previous studies showed that impaired NK cell activity was found in family members of patients with different types of cancer ( 40, 41, 42 ). Importantly, such inherited defects in NK cells, APP and Wnt pathways were repeatedly observed between non-cancer and cancer individuals (Fig 2b, Supplementary Fig 9), between TIME-rich and TIME-intermediate/-poor patients (Fig 2a, Supplementary Fig 4, Fig 1d), suggesting that these individuals were highly selected for tumorigenesis and metastasis.…”
Section: Resultssupporting
confidence: 67%
“…The study by Imai et al on an 11-year followup of 3,625 residents of a Japanese community for their immune cell profile indicated that medium and high cytotoxic activity of peripheral-blood lymphocytes is correlated with a decrease in cancer risk, whereas low activity is correlated with an elevated cancer risk (5). In their study, Montelli et al concluded that NK-cell activity is decreased in family members of patients with various types of cancer compared to healthy controls of similar parameters (6). Similarly, the study by Dewan et al revealed that NK activity of PBMNCs is lower in breast cancer patients (21).…”
Section: Discussionmentioning
confidence: 98%
“…The detailed results of the PBMNC cell counts, cell expansion details and the percentage of CD3-CD56+ cells are shown in Table I 6 cells, respectively. The average percentage of CD3-CD56+ cells on the day of maximum growth or the day of harvesting in Case I following in vitro expansion was 1.2%, while in Case II it was 65.7%; in Case III it was 28.63%, in Case IV it was 65.9% and in Case V it was 40%.…”
Section: Patient Characteristics and In Vitro Cell Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the lytic unit does not address the matter of NK cell frequency in the assay system; rather, it should be regarded as a reasonable proxy for the percent lysis generated at various E/T ratios. In contrast, an agarose gel or poly-L-lysine hydrobromide polymer-based cell cytotoxicity assay system, in which effector cell/target cell conjugates are made and then the degree of effector cells bound to target cells is measured as a percentage to determine NK cell activity, may resolve the NK cell frequency effect (31,32). This method deals with single-cell activity conceptually equivalent to the lytic index.…”
Section: Discussionmentioning
confidence: 99%